Gérard Dion, 1912-1990 - Thwaites, James (Labour / Le Travail, 1991)
The article pays homage to the life and work of Gérard Dion, who for decades played a pivotal role in the department of industrial relations at Laval University as well as its journal, Relations industrielles/Industrial Relations. A Catholic priest, Dion, who also held degrees in sociology and theology, wrote extensively on labour and industrial relations, and was involved at a number of levels in Quebec society. He was the recipient of honours and awards, including the Order of Canada. A photo of Dion is included.
Keywords: DION; Gerard; Obituaries

In Memoriam – Eugene Forsey 1904-1991 - Thwaites, James (Relations industrielles / Industrial Relations, 1991)
Offers a tribute to Forsey's life and work – scholar, labour and political activist, and media commentator.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z